Dissecting the Role of Substrate on the Morphology and Separation Properties of Thin Film Composite Polyamide Membranes: Seeing Is Believing - Peng, Lu Elfa; Yao, Zhikan; Yang, Zhe; Guo, Hao; Tang, Chuyang Y (Environmental science & technology, 2020)
Recent studies show that the surface morphology of a thin film composite (TFC) polyamide membrane depends strongly on its porous substrate. Nevertheless, the underlining mechanisms and the effects on membrane separation performance remain controversial. To dissect the exact role of pore properties, we synthesized TFC polyamide membranes on polycarbonate substrates with cylindrical track-etched pores (PCTE) of well-defined pore size ranging from 10 to 800 nm. Leaf-like roughness features were most prominent for polyamide films formed on substrates of intermediate pore sizes (80 and 100 nm). Smaller pores inhibited leaf-like features as a result of insufficient storage of -phenylenediamine (MPD) monomers for the interfacial reaction, whereas larger pores resulted in diminished surface roughness due to the lack of confinement to the interfacially degassed nanobubbles. Substrate porosity plays a critical role on membrane water permeability, while smaller pores with greater pore density are favored to improve membrane rejection. TFC polyamide membranes prepared on sponge-like poly(ether sulfone) and polysulfone substrates exhibit better water permeability and salt rejection compared to the PCTE-TFC membranes thanks to the simultaneously enhanced confinement and MPD storage effects. The mechanistic insights gained in this study reveal the huge potential of substrate design toward high-performance TFC RO membranes.